Minutes of pre-bid meeting with the bidders of Busbar Trunking (BBT) system for BRACU new campus project - Brac University (Brac University, 2023)
Minutes of the pre-bid meeting with the bidders Busbar Trunking (BBT) System for BRACU new campus, held on 5th March, 2020.